Psychological Tendencies of Personal Manifestations of Students with Different Life Roles - Odintsova, Anastasiia (Psychological Prospects Journal, 2014)
The results of empirical study on the relationship between the type of vital role and manifestations of human personality are highlighted in the article by Odintsova A. N. «Psychological tendencies personal manifestations of students who have different types of vital roles». The paper presents a typology of private vital roles, which is based on comparison of the concept of «role» with terms such as «life position», «life line», «life strategy», «meaning of life» and «life perspective». The typology of roles on the concept of individual life path is represented as a pair of constructs: axiological-semantic – axiological-neutral role, consistent and inconsistent role, active and passive roles, sense-creative and sense-neutral role, conscious and unconscious role. In the main part of the paper presents the results of the study, this was attended by students aged 18 to 22 years. Of empirical research methods were used: author profile «Attitude to the own role» methodology of multivariate study of personality Cattell (form C), test «Meaning-life orientation», methods of COS and coping-test Lazarus. Relationship between the dominant type of vital role, of personal qualities, commitment, a way of overcoming the difficulties of life, the level of communication and organizational skills is empirically revealed. The results of the factor analysis identified three factors that permitted us to analyze the different attitudes towards their role. To the first, together with the personal indicators, included «active – passive» vital roles; the second – «consistent and inconsistent», «sense-creative and sense-neutral» and «conscious and unconscious» roles; the third group – «axiological-semantic – axiological-neutral» vital roles. Identified three perspectives on the performance of the role, namely, they are: role as the process of active or passive interaction; the role, as a mean to achieve a goal; the role, as a way of expression. The scientific novelty of the material obtained lies in the fact that for the first time at the empirical level has been investigated the relationship between the type of the vital role and manifestations of human personality. The results can be used to create programs and optional training sessions.